Relation of availability and barley uptake of some potentially toxic elements - Fodor, László (Acta Agraria Debreceniensis, 2008)
A small-plot microelement load field trial was set up on brown forest clay soil with eight elements (Al, As, Cd, Cr, Cu, Hg, Pb, Zn), on 3 levels each (0/30, 90, 270 kg element ha-1). The soil was treated with soluble salts of elements once at initiation (1994). In the seventh year of the experiment (2001) winter barley was the test plant. The total element content was determined in plant samples (shoot, straw, grain) after microwave digestion using cc.HNO3+cc.H2O2. The element composition of the prepared samples was determined using ICP-MS technique. In the experiment toxic effects of treatments and yield loss could not be observed. Zn and As contents in barely shoots were only moderately increased by increasing microelement loads. Effects of Cr, Cu, Hg, Pb and Al treatments could not be observed. On the other hand, Cd accumulation was significant in the shoot. Cd content was also increased both in straw and grain. Results of this experiment prove that Cd remains mobile in the soil-plant system for a long time. Its accumulation can be observed both in vegetative and reproductive parts of plants without toxic symptoms and yield loss.